ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PENDIDIKAN (ANGKA PARTISIPASI MURNI), KESEHATAN (ANGKA KEMATIAN BAYI DAN BALITA) TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN/KOTA PROPINSI KALIMANTAN BARAT - B01108050, Margening Rahayu (Jurnal Curvanomic, 2012)
The purpose of this research was to determine the effect of economic growth, education (Pure Participation Number), health (Infant and child mortality) rate of the Human Development Indexs in the District/city of West Kalimantan Province. The method used was ordinary least square model using panel data (cross section and time series) by using common effect. Observation data as much as 50 in 10 Districts/cities of West Kalimantan Province during the period 2006 to 2010, data processing computer program using E-views 4. The results of this research indicate that the enrollment rate Pure Participation Number SMP/MTs gave a positive and significant influence on the Human Development Index in the District/city of West Kalimantan Province. Economic Growth, Pure Participation Number SD/MI gave a unsignificant and negative effect on the Human Development Index District/city of West Kalimantan Province negatively affect the Human Development Index in the District/city of West Kalimantan Province, while the Pure Participation Number SMA/MA and Infant and Child Mortality gave a positive and unsignificant influence on the Human Development Index in the District/city of West Kalimantan Province. Keywords: Human Development Index, Economic Growh, Pure Participation Number, Infant And Child Mortality.